Kebijakan Redaksi Media Dakwah dalam Membangun Kerukunan Ummat Beragama di Jawa Barat - Roni Tabroni (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
This study examines the media dakwah in the form of mosque bulletin relation to harmony religious community in West Java. Some years ago the media reported that West Java is the province with the highest rate of inter-religious conflict in Indonesia. Resistance to physical violence is very likely one of them caused by the low level of understanding of the ummah against religious insight. This research is important to assess whether in the form of bulletin dakwah media has a role in preventing conflict, or even contribute to lower levels of religious harmony in West Java community. The method used research is qualitative with descriptive approach. By taking Uswah bulletin issued by Pusdai West Java and bulletins issued by the Gema Mujahidin by Muhammadiyah West Java. The study produced findings on historical aspects, management, and message bulletin dakwah . Content that has been developed and become a mainstream issue in the two bulletins in the form of community enlightenment through the messages of Islam are moderate and more peaceful. The second bulletin became a tool for community education about the importance of tolerance and Islamic deeper insight. Bulletin becomes adhesive media community as well as building human civilization through the message of Islam is universal.